CRITERIA FOR REHABILITATION OF FACILITIES AND TERRITORIES CONTAMINATED WITH RADIONUCLIDES AS A RESULT OF PAST ACTIVITIES: PART 1. THE CHOICE OF INDICATORS FOR JUSTIFICATION OF THE CRITERIA FOR REHABILITATION - I. K. Romanovich; I. P. Stamat; N. I. Sanzharova; A. V. Panov (Радиационная гигиена)
The article examines issues of rehabilitation of facilities and territories contaminated by the man-made and natural radionuclides as a result of past activities of enterprises of nuclear and non-nuclear industries. Rehabilitated facilities and territories contaminated with radionuclides as a result of past activities of enterprises must meet criteria based on the analysis of requirements of existing normative legislative documents in the field of radiation protection of the population taking into account the recommendations of international organizations that are justified dose quantities and derivative indicators used in criteria setting. It is shown that the criteria for rehabilitation of facilities and territories contaminated by man-made radionuclides as a result of past activities, should be the same regardless of whether the contamination occurred as a result of planned activities of the enterprise or due to unauthorized activities. For these situations, the criteria for rehabilitation should be based on dose quantities and derived indicators of the residual contamination of the environment after rehabilitation. Only indicators of radiation safety of the environment can be used in almost all cases for justification of the criteria for rehabilitation of facilities and territories contaminated by natural radionuclides. The article shows that such approaches are applicable not only to environmental media contaminated as result of past activities of enterprises of traditional non-nuclear industries but the mining of uranium and thorium ores. From the standpoint of modern classification of industrial waste with a high concentration of natural radionuclides, the characteristics of these wastes according to their potential radiation hazard to people and the environment are identical.